Textbook citizenship the depiction of citizenship in selected social studies High School Textbooks in Iloilo City . - Almio, Doni June V. (2012.)
A research was conducted to identify the citizenships depicted in selected Social Studies textbooks in Iloilo City and compared it with the citizenships found in Russia in Bulgaria. The method used for the study was qualitative content analysis of sixteen social studies textbooks and key informant interview for the process is the state through its agencies. The schools may it be public, laboratory, or private are subjected to the guidelines of the Department of education when it comes to selection of textbooks. The researcher identified four classifications of citizenship, National Citizenship, and Religious Citizenship. These classification of citizenship depicted in the high school social studies textbooks, it will be evident on how the Philippines wants its citizens to be. This is because of the reason that Philippines used the textbooks as state ideological apparatuses to maintain control over its people. Citizenship is the best way to do that
Research Paper (Undergraduated, Bachelor of Arts in Political Sciences - Management) College of Arts and Sciecnes, University of the Philippines Visayas, Miagao, Iloilo. 2012.
Keywords: Textbook -- Social Studies -- Iloilo City